Compositional Design, Microstructure, and Thermal Processing of Aluminum-Based Complex Concentrated Alloys - Spyridon Chaskis; Constantinos Tiktopoulos; Evangelos Gavalas; Marianthi Bouzouni; Fotis Tsiolis; Spyros Papaefthymiou (Crystals)
Three lightweight aluminum-based complex concentrated alloys with chemical compositions that have not been previously studied were manufactured and studied: Al52Mg9.6Zn16Cu15.5Si6.9 w.t.% or Al63Mg13Zn8Cu8Si8 a.t.% (alloy A), Al44Mg18Zn19Cu19 w.t.% or Al55Mg25Zn10Cu10 a.t.% (alloy B), and Al47Mg21.4Zn12Cu9.7Si9.7 w.t.% or Al52.7Mg26.6Zn5.6Cu4.6Si10.4 a.t.% (alloy AM), with low densities of 3.15 g/cm3, 3.18 g/cm3 and 2.73 g/cm3, respectively. During alloy design, the CALPHAD method was used to calculate a variety of phase diagrams for the various chemical compositions and to predict possible phases that may form in the alloy. The CALPHAD methodology results showed good agreement with the experimental results. The potential of the designed alloys to be used in some industrial applications was examined by manufacturing them using standard industrial techniques, something that is a rarity in this field. The alloys were produced using an induction furnace and pour mold casting process, while industrial-grade raw materials were utilized. Heat treatments with different soaking times were performed in order to evaluate the possibility of improving the mechanical properties of the alloys. Alloys A and AM were characterized by a multiphase microstructure with a dendritic FCC-Al matrix phase and various secondary phases (Q-AlCuMgSi, Al2Cu and Mg2Si), while alloy B consisted of a parent phase T-Mg32(Al,Zn)49 and the secondary phases α-Al and Mg2Si. The microstructure of the cast alloys did not appear to be affected by the heat treatments compared to the corresponding as-cast specimens. However, alterations were observed in terms of the elemental composition of the phases in alloy A. In order to investigate and evaluate the mechanical properties of the as-cast and heat-treated alloys, hardness testing along with electrical conductivity measurements were conducted at room temperature. Among the as-cast samples, alloy AM had the highest hardness (246 HV4), while among the heat-treated ones, alloy A showed the highest value (256 HV4). The electrical conductivity of all the alloys increased after the heat treatment, with the highest increase occurring during the first 4 h of the heat treatment.